Faktor - faktor yang mempengaruhi minat penggunaan e-filling oleh wajib pajak pribadi sebagai sarana pelaporan SPT masa secara online dan realtime - Diah Pitaloka, Harlinda Mei; Bagana, Batara Daniel (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the interest in using e-Filling by using perceptions of convenience, perceived usefulness, perceptions of security and confidentiality, and also the readiness of information technology. The type of data used in this study uses quantitative data. This research was conducted on taxpayers who are in the West Semarang KPP Pratama area. The population in this study were taxpayers in West Semarang who actively used e-Filling, amounting to 1,237 people, while the sample in this study amounted to 100 respondents. The data analysis technique used multiple regression with SPSS tools. The results showed that Perception of Ease had a significant effect on Interest in Using e-Filling, Perception of Use had a significant effect on Interest in Using e-Filling, Perception of Security and Confidentiality had no significant effect on Interest in Using e-Filling, Perception of Information Technology Readiness had no significant effect on Interest in Use. e-Filling.